EFFECT OF JUDO KATA TRAINING ON BALANCE OF JUDO PLAYERS AGED 17 TO 19 YEARS BOYS - Gupta, Rajkumar C.; Pravin, Sayyed Asma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the effect of Judo Kata training on the balance of college students aged 17 to 19. A total of 70 male students from Prakash College, Kandivali (W), were divided into two groups: an experimental group and a control group, each consisting of 35 participants. Using a pre-test and post-test non-equivalent control group design, the experimental group underwent Training focused on Judo Kata for 16 weeks, while the control group received no such training. Balance was measured using the Stork Stand test, with data analyzed using One Way ANCOVA. The results indicated a significant difference in the adjusted mean scores of balance between the experimental group (mean = 6.694) and the control group (mean = 6.106), with an F-value of 9.545 which is significant at 0.05 level. This suggests that Judo Kata training effectively improves balance among judo players. Consequently, the null hypothesis—stating no significant difference in balance between the two groups—was rejected. The findings highlight the importance of Judo Kata training in enhancing balance, contributing to the holistic development of judo players.